Development and validation of a distress measurement for insulin injections among patients with diabetes - Eujin Choi; Min-Sun Kim; Juhee Cho; Sooyeon Kim; Eun Kyung Kwon; Youngha Kim; Danbee Kang; Sung Yoon Cho (Scientific Reports, 2023)
Abstract Insulin injections are stressful but necessary for people with diabetes. This study aimed to develop and validate the Distress of Self-Injection (DSI) scale for patients with diabetes aged ≥ 10 years. We created a questionnaire to evaluate DSI after examining each item following a literature review. The DSI scale with 20 questions in three domains (physical [4], psychosocial [7], and process [9]) was developed and tested at the Samsung Medical Center in Seoul, Korea, from April to September 2021. To verify structural validity, exploratory and confirmatory factor analyses (CFA) were conducted. Internal consistency was also calculated. To assess construct and criterion validity, the correlation between the DSI scale and Korean version of the Problem Areas in Diabetes (PAID-K) scale was obtained. Cronbach’s alpha varied from 0.69 to 0.87, and the DSI score was 0.90, demonstrating acceptable internal consistency. CFA fit indices (CFI = 0.980; RMSEA = 0.033) were favorable. DSI and pertinent PAID-K domains correlated strongly. For measuring self-injection distress, the DSI score had good accuracy. For patients with diabetes aged ≥ 10 years who self-inject insulin, the DSI was a viable and accurate method for quantifying discomfort associated with insulin injection. Health practitioners should use the DSI to communicate with patients about their suffering.